A study of lecturers' views and the obstacles in ICT integration in UiTM Terengganu / Yazarina Yahya - Yahya, Yazarina (2014)
As Malaysia is moving towards becoming a developed nation by the year 2020, institutions of higher learning in Malaysia are vigorously implementing policies to integrate ICT into their curriculum. Lecturers have been instructed to integrate ICT in their classrooms. In order to gain a better understanding about the lecturers' roles as good models of employing ICT in language classrooms, it is important to find out their views and attitudes about ICT in their classrooms. This is because by gaining an insight into their views, then only researchers were able to get a better understanding how they used ICT and how they might be helped to develop their potential more effectively for teaching and research. This study specifically investigated lecturers' views on ICT integrations in teaching English as a second language (ESL) in a public university in Terengganu. It also examined the challenges they faced in using computers in teaching English. Based on the feedback gathered from the questionnaires, the findings showed that the lecturers' views toward integrating computer were very positive indeed in which responses showed a high level of agreement (ie. M=3.30). In addition, they did not face many challenges which affected their effective utilization of ICT in their English classes. The results obtained from the study suggested that constructivism learning theory should be the basis for ICT integration. Other suggestions given are that there should be collaborative work amongst the lecturers and strong ongoing support in the instructional and administrative aspects of IT in the institution, so as to enable lecturers to embrace IT fully in English language teaching in their classrooms. Finally, this paper provided some implications of the study so that lecturers could make adjustments to their teaching methodology which would lead to effective ICT integration in the teaching and learning of the English language.